Development Of Ternary Ni-Ag-P And Ni-Cu-P Using Electroless Coating On Copper Substrate - Md Sani, Nur Ariffah (2015)
Current functional test of assembled device in semiconductor industry use thermal interface media but it occasionally caused cosmetic defects such as stain or scratch mark. A possible solution to eliminate the undesired defects is by improving the nickel-phosphorus (Ni-P) coating currently applied on the test chuck in terms of the ability to conduct heat transfer efficiently and thus eliminate the use of thermal interface media. Co-deposition of argentum (Ag) and copper (Cu) into Ni-P coating are expected to improve the thermal conductivity of Ni-P coating without sacrificing other coating’s properties; surface roughness, thickness, hardness and wear resistance. Ni-P coating in this work was prepared via electroless coating on a copper substrate. The experimental work began by developing the coating solution in order to achieve targeted phosphorus content, thickness and surface roughness. To produce ternary nickel-argentum-phosphorus (Ni-Ag-P) and nickel-copper-phosphorus (Ni-Cu-P) coating, argentum and copper salt were added into the coating solution. The best ternary coating was observed on coating containing 5 mg/L argentum sulphate and 10 mg/L copper sulphate with co-deposition of 1.14 wt.% Ag and 3.56 wt.% Cu respectively. Both ternary coating produced have smoother surface with lower wear rate compared to binary Ni-P coating. Improvement in wear resistance is related to the hardness of coating, in which Ni-Ag-P has highest hardness (394.08 HK) followed by Ni-P (380.78 HK) and Ni-Cu-P (365.34 HK). Even though Ni-Cu-P coating possess low hardness, its low surface roughness contributed to the low wear rate. The thermal conductivity for ternary Ni-Ag-P coating (451.10 W/m.K) was higher than Ni-P (445.70 W/m.K) and Ni-Cu-P coating (326.91 W/m.K). The result is as expected as argentum has higher conductivity compared to nickel, and thus addition of argentum is able to improve thermal conductivity of Ni-P coating.